Adult attention deficit hyperactivity symptoms and psychosis: Epidemiological evidence from a population survey in England. Issue 1 (30th September 2015) - Marwaha, Steven; Thompson, Andrew; Bebbington, Paul; Singh, Swaran P.; Freeman, Daniel; Winsper, Catherine; Broome, Matthew R.
Abstract: Despite both having some shared features, evidence linking psychosis and adult attention deficit hyperactivity disorder (ADHD) is sparse and inconsistent. Hypotheses tested were (1) adult ADHD symptoms are associated with auditory hallucinations, paranoid ideation and psychosis (2) links between ADHD symptoms and psychosis are mediated by prescribed ADHD medications, use of illicit drugs, and dysphoric mood. The Adult Psychiatric Morbidity Survey 2007 ( N =7403) provided data for regression and multiple mediation analyses. ADHD symptoms were coded from the ADHD Self-Report Scale (ASRS). Higher ASRS total score was significantly associated with psychosis, paranoid ideation and auditory hallucinations despite controlling for socio-demographic variables, verbal IQ, autism spectrum disorder traits, childhood conduct problems, hypomanic and dysphoric mood. An ASRS score indicating probable ADHD diagnosis was also significantly associated with psychosis. The link between higher ADHD symptoms and psychosis, paranoia and auditory hallucinations was significantly mediated by dysphoric mood, but not by use of amphetamine, cocaine or cannabis. In conclusion, higher levels of adult ADHD symptoms and psychosis are linked and dysphoric mood may form part of the mechanism. Our analyses contradict the traditional clinical view that the main explanation for people with ADHD symptoms developing psychosis is illicit drugs. Highlights: Hypotheses that adult ADHD symptoms and probable ADHD diagnosis are associated with psychosis were tested. Potential mediating factors were explored. Higher ADHD symptom load was significantly associated with psychosis, paranoid ideation and auditory hallucinations despite controlling for important covariates. The link between higher ADHD symptoms and psychosis variables was significantly mediated by dysphoric mood, but not by use of amphetamine, cocaine or cannabis. The number of adults taking medications for ADHD was very small and statistical testing to assess the link with psychosis was not possible. The analyses contradict the traditional clinical view that the main explanation for people with ADHD symptoms developing psychosis is illicit drugs.